Gelation Properties of Okra’s Extract and Its Application in Strawberry Jam - Kamdee, Supinan; Pornprasop, Vanvimon; Sompongse, Warangkana (Thai Journal of Science and Technology, 2023)
This research was to study application of okra’s extract (Abelmoschus esculentus (L.) Moench) to reduce sucrose content in strawberry jam. Optimum temperature for extraction of okra was investigated in 4 levels: 50, 60, 70 and 80°C. Physical analysis was determined by % yield, flowing distance and color values (Hunter L* a* b*). It was found that the optimum temperature for extraction was 60°C. Then, gelation properties of okra’s extract was investigated in 3 concentration levels of sucrose: 50, 60 and 70% (by weight of sugar per weight of okra’s extract) and 3 concentration levels of calcium chloride: 2, 2.5 and 3% (by weight of calcium chloride per total weight). Physical analysis was determined by flowing distance and color values (Hunter L* a* b*). It was found that ratio of sugar to calcium chloride at 50:2 had the least flowing distance (or the highest viscosity). Therefore, this ratio was used to study an appropriate ratio of okra’s extract to reduce sucrose content in strawberry jam. Okra’s extract content was varied in 3 levels: 20, 40 and 60% (by weight of Okra’s extract per total sucrose weight) and pectin content was varied in 2 levels: 0.5 and 1% (by total weight). It was indicated that ratio of sucrose to okra’s extract to pectin at 40:60:0.5 had the most spreadability and the highest flowing distance (or the least viscosity). Sensory evaluation were higher score in appearance and spreadability than that of the control sample. Therefore, this formula was selected to study chemical composition. The proximate analysis were 60.75±0.95% moisture, 0.45 ± 0.02% fat, 0.49 ± 0.01% fiber, 0.59 ± 0.02% protein, 4.26 ± 0.19% ash and 33.47 ± 0.76% carbohydrate by wet basis. The strawberry yam with ratio of sucrose to okra’s extract to pectin at 40:60:0.5 had the energy from calculation 31.49 % lower than that of the control sample. Keywords: Okra’s extract; Yam product; Sugar; Calcium; Pectin; Gelation properties